2003
DOI: 10.1596/1813-9450-2967
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Poverty in Guatemala

Abstract: The objective of this paper is to document the extent and impact of income and of intergenerational effects. distribution of child and adult malnutrition in Education of adults in the household and the availability Guatemala; to analyze the relationship between selected of infrastructure are other important determinants of child, maternal, household and community children's growth attainment. Finally, even controlling characteristics and children's nutritional status; and to for income and other household and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 26 publications
2
41
0
2
Order By: Relevance
“…Within this reasoning however, there is an assumption that the mains water will be safe to drink. While many studies recognise the importance of increasing the availability of water to reduce rates of malnutrition (10) , it is equally important to ensure the quality of the water supply. The Guatemalan Ministry of Health has recently reported that 98 % of the country's water sources are contaminated in some way (18) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this reasoning however, there is an assumption that the mains water will be safe to drink. While many studies recognise the importance of increasing the availability of water to reduce rates of malnutrition (10) , it is equally important to ensure the quality of the water supply. The Guatemalan Ministry of Health has recently reported that 98 % of the country's water sources are contaminated in some way (18) .…”
Section: Discussionmentioning
confidence: 99%
“…While there is much evidence describing the impact and effective treatment of malnutrition using these volunteer-run clinics in pre-school children (9,10) , little y Correspondence address: 56 Farnham Road, Guildford, Surrey, GU2 4PE, UK. evidence exists to suggest whether these strategies are also effective in schoolchildren in Guatemala.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1996, Bose andAcosta-Belén 1995). Community development must differentiate between the needs and interests of the community as a whole and the needs and interests of women and children in particular (Marini and Gragnolati 2003).…”
Section: Women and Community Developmentmentioning
confidence: 99%
“…A peopleoriented approach to development that is gender sensitive not only avoids perpetuating existing problems but works against the effects of discrimination (Sweetman 2002). As well as affecting the economic output of a community, empowering women enhances child health, food production and lowers population growth rates resulting in a better quality of life for women and, therefore, their families (Marini andGragnolati 2003, Sharma 2001). …”
Section: Empowering Women Leads To Community Developmentmentioning
confidence: 99%